Odpowiedzi

Najlepsza Odpowiedź!
2010-01-27T15:29:00+01:00
A) a + (a-b)=a+a-b=2a-b
b) 2x - (x + 4)=2x-x-4=x-4
c) 7 - (- x + 6)=7+x-6
d) - (x + 4) + (x - 5 )=-x-4+x-5=-9
e) 1 - (t + p) - (t - 2) = 1-t-p-t+2=3-2t-p
f) -(-y + 2) + (-2y - 4) = y - 2 -2y - 4= -y -6
2010-01-27T15:30:11+01:00
A) a + (a-b)=a+a-b=2a-b
b) 2x - (x + 4)=2x-x-4=x-4
c) 7 - (- x + 6)=7+x-6=x-1
d) - (x + 4) + (x - 5 )=-x-4+x-5=-9
e) 1 - (t + p) - (t - 2)=1-t-p-t+2=3-2t-p
f) -(-y + 2) + (-2y - 4)=y-2-2y-4=-y-6
2010-01-27T15:31:51+01:00
A) a + (a-b)= a+a-b = 2a-b
b) 2x - (x + 4) = 2x-x-4= x-4
c) 7 - (- x + 6)= 7+x-6= 1+x
d) - (x + 4) + (x - 5 )= -x-4+x-5= -9
e) 1 - (t + p) - (t - 2)= 1-t-p-t+2= 3-2t-p
f) -(-y + 2) + (-2y - 4)= y-2-2y-4= -y-6